Italy : Technical Note on Interconnectedness and Spillover Analysis. (IMF Staff Country Reports; Country Report ;, 2013)
This Technical Note discusses findings of interconnectedness and spillover analysis on Italy. The market-based measures of tail risks and interconnectedness among key banks and insurance companies in Italy have declined from their peak but remain at elevated levels. Although the stress on Banca Monte dei Paschi di Siena has been manifesting on its own, the market perception about the condition of the banks appears to be increasingly contaminating the market views on other Italian financial institutions. It is also observed that exogenous factors, such as the Italian sovereign, are the key source of systemic risk for the market pricing of Italian financial institutions.